2015
DOI: 10.3389/fenrg.2015.00037
|View full text |Cite
|
Sign up to set email alerts
|

Radioactive Cs in the Severely Contaminated Soils Near the Fukushima Daiichi Nuclear Power Plant

Abstract: Radioactive Cs isotopes (137 Cs, t 1/2 = 30.07 years and 134 Cs, t 1/2 = 2.062 years) occur in severely contaminated soils within a few kilometer of the Fukushima Daiichi nuclear power plant at concentrations that range from 4 × 10 5 to 5 × 10 7 Bq/kg. In order to understand the mobility of Cs in these soils, both bulk and submicron-sized particles elutriated from four surface soils have been investigated using a variety of analytical techniques, including powder X-ray diffraction analysis, scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The OTZ3 and OTZ10 were separated from the same soil collected from the top ~1 cm of the paddy soil at Ottozawa located ~4 km west from the FDNPP in Okuma Town, Futaba County, Fukushima, on March 16, 2012. The soil was mainly composed of clay minerals, quartz, and feldspar 9 . Because it is still prohibited to enter the area due to the high radiation dose, the locality remained untouched and was not disturbed by decontamination or restoration.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The OTZ3 and OTZ10 were separated from the same soil collected from the top ~1 cm of the paddy soil at Ottozawa located ~4 km west from the FDNPP in Okuma Town, Futaba County, Fukushima, on March 16, 2012. The soil was mainly composed of clay minerals, quartz, and feldspar 9 . Because it is still prohibited to enter the area due to the high radiation dose, the locality remained untouched and was not disturbed by decontamination or restoration.…”
Section: Methodsmentioning
confidence: 99%
“…The gravel samples were carefully collected from the ground surface using a hand shovel and placed in plastic bags. The soil was also mainly composed of clay minerals, quartz, and feldspar 9 . The third sample (OMR1) was collected under the drainpipe of the warehouse in Omaru located in Namie Town, Futaba County, Fukushima, ~10.5 km northwest from the FDNPP during the sampling campaign on December 20, 2012.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of this it is easily detected by gamma ray emission during the isomeric transition. Many researchers have suggested that the occurrence and geochemical behavior of radioactive Cs (mainly 134 Cs and 137 Cs) in the surface environment is critical to predicting its distribution and subsequent radiation exposures (Ueda et al, 2013;Kato et al, 2012;Aoyama et al, 2012;Tazoe et al, 2012;Kaneko et al, 2015).…”
Section: Introductionmentioning
confidence: 99%